Plastic-associated harmful microalgal assemblages in marine environment. (January 2019) - Casabianca, Silvia; Capellacci, Samuela; Giacobbe, Maria Grazia; Dell'Aversano, Carmela; Tartaglione, Luciana; Varriale, Fabio; Narizzano, Riccardo; Risso, Fulvia; Moretto, Paolo; Dagnino, Alessandro; Bertolotto, Rosella; Barbone, Enrico; et al.
Abstract: Plastic debris carry fouling a variety of class-size organisms, among them harmful microorganisms that potentially play a role in the dispersal of allochthonous species and toxic compounds with ecological impacts on the marine environment and human health. We analyzed samples of marine plastics floating at the sea surface using a molecular qPCR assay to quantify the attached microalgal taxa, in particular, harmful species. Diatoms were the most abundant group of plastic colonizers with maximum abundance of 8.2 × 10 4  cells cm −2 of plastics, the maximum abundance of dinoflagellates amounted to 1.1 × 10 3  cells cm −2 of plastics. The most abundant harmful microalgal taxon was the diatom Pseudo-nitzschia spp., including at least 12 toxic species, and the dinoflagellate Ostreopsis cf. ovata with 6606 and 259 cells cm −2, respectively. The abundance of other harmful microalgal species including the toxic allochthonous dinoflagellate Alexandrium pacificum ranged from 1 to 73 cells cm −2 . In the present study, a direct relationship between the abundance of harmful algal species colonizing the plastic substrates and their toxin production was found. The levels of potential toxins on plastic samples ranged from 10 1 to 10 2  ng cm −2, considering the various toxin families produced by the colonized harmful microalgal species. We also measured the rate of adhesion by several target microalgal species. It ranged from 1.8 to 0.3 day −1 demonstrating the capacity of plastic substrate colonizing rapidly by microalgae. The present study reports the first estimates of molecular quantification of microorganisms including toxin producing species that can colonize plastics. Such findings provide important insights for improving the monitoring practice of plastics and illustrate how the epi-plastic community can exacerbate the harmful effects of plastics by dispersal, acting as an alien and toxic species carrier and potentially being ingested through the marine trophic web. Graphical abstract: Image 1 Highlights: Toxic microalgal species colonized on marine plastic debris. Colonized toxic microalgal taxa on marine plastics was quantified by qPCR. Pseudo-nitzschia spp. were the predominant microalgal taxon on marine plastics. Concentrations of toxins on marine plastics ranged from 10 1 to 10 2  ng cm −2 . Harmful Algal species can be dispersed through plastics in marine environment.